Second European quality of life survey living conditions, social exclusion and mental well-being - Layte, Richard; Maitre, Bertrand; Whelan, Christopher T.; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2010)
Over the past two decades, there has been a major shift in the European debate regarding social progress and how it is measured. The concept of social exclusion has increasingly replaced the concept of poverty within the EU policy discussion on social vulnerability and disadvantage. Unfavourable labour market access and living conditions affect both social participation and social contact, which in turn impact on the quality of life of Europe's citizens and influence their perception of social exclusion. The second European Quality of Life Survey (EQLS), conducted by the European Foundation for the Improvement of Living and Working Conditions (Eurofound) in 2007, offers a wide-ranging view of the diverse social realities in the 27 EU Member States, as well as covering Norway and the candidate countries of Croatia, the former Yugoslav Republic of Macedonia and Turkey.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Social surveys -- European Union countries; Europe -- Social conditions -- 21th century; Electronic books